Communicating 'normal' behaviour: a randomised controlled trial experimenting with plastic avoidance media messages. Issue 4 (2nd October 2022) - Borg, Kim; Curtis, Jim; Lindsay, Jo
ABSTRACT: When excerpts from documentaries about plastic waste are shared on social media, they can increase problem awareness among millions of users. However, they can also inadvertently discourage plastic avoidance by emphasising the scale of the problem and undesirable social norms. An online experiment was undertaken with 1, 001 respondents to test if exposure to social media friendly video clips from documentaries about plastic waste influenced plastic avoidance perceptions and behaviours. While social norm perceptions differed depending on how the issue was presented and who delivered the message, the clips were most effective in sensitising the market by promoting the benefits of avoidance, increasing policy support, and increasing willingness to communicate about the issue. The theoretical and practical implications are discussed.